Seed Policy in Colombia (2014)
This paper aims to give an overview of the new seed policy in Colombia based on the peasant's tradition that collect the best products for future harvests contrasting with the new schemes where this practice is condemned by the law due to the increasing integration of Colombia to the global economy and the establishment of a seed monopoly based on the protection of intellectual property. This text also examines the implications of the use of genetically modified seeds and their effects on biodiversity, legislation, culture and economy.